Overview of the use of geotechnologies and cartographic map bases in the municipalities of Espírito Santo, Brazil - Fábio Luiz Mação Campos (Geografares, 2022)
Geotechnologies have shown to be important and promising tools for improving public management, but publications about their use in Brazilian municipalities are rare. This research carried out a survey on the use of geotechnologies and the existence and use of cartographic map bases in the municipalities of Espírito Santo state through questionnaires answered by the city halls. The results showed that there is a strong demand for updating cartographic bases and that the use of geoprocessing tools can be greatly expanded. Paths and strategies for this expansion were pointed out, in addition to some experiences of the municipalities and opportunities for action for professionals and institutions in the area of geotechnology. The work can be used to outline the use of geotechnologies in Brazilian municipalities and assist in the construction of projects aimed at these public bodies.
Keywords: geotechnologies; cartographic map bases; public administration